TEACHER STRATEGIES IN IMPROVING THE UNDERSTANDING OF MULTIPLICATION AND DIVISION MATERIAL IN THE MATHEMATICS SUBJECT OF GRADE 3 STUDENTS AT THE INTEGRATED MUHAMMADIYAH ELEMENTARY SCHOOL IN PONOROGO - Honesty Putri Titani; Nurul Abidin; Wawan Kusnawan (Prima: Jurnal Pendidikan Matematika, 2026)
Mathematics learning in elementary schools has been a challenge to teachers and to students in lower grades due to the nature of the subject and the need to build a strong understanding base. The strategies applied by the teachers can be an important factor to help the students understand the subject of mathematics more effectively and impactfully. This article aims to discuss the strategies applied by the teachers to help the third-grade students of Muhammadiyah Terpadu Elementary School Ponorogo understand the subject of multiplication and division while also mentioning the supporting and hindering factors encountered during the process. This research applied a qualitative research method with a descriptive approach to collect the information. Information collection was carried out through interviewing the three math teachers of the third-grade students as the main participants, while observations were also carried out to directly witness the math learning process among the students. Information analysis was carried out through the application of the following steps: data reduction, presentation, and conclusion drawing. The results revealed that the educators used different strategies to improve students' understanding of the material, including the use of educational aids, interactive learning games, and individual strategies to assist students who had difficulties with their understanding. The factors that supported students' learning of multiplication and division include educational aids, teachers' support, and apperception to motivate students to recall previous lessons. The factors that hinder students' mastery of multiplication and division skills include: 1) lack of interest to memorize, 2) gadgets' dependency, and 3) students' peers. From the findings of the research, it can be concluded that the use of different strategies and students' involvement in the learning process can improve their understanding of multiplication and division skills among third-grade students. Effective strategies used by teachers play a significant role in creating a more meaningful and enjoyable experience of learning mathematics among elementary school students.